Jak żyć w pułapce post-cielesności? - Bogusława Bodzioch- Bryła (Jesuit University Ignatianum in Krakow, 2017)
The text pays attention to the importance of the body category and the necessity to treat the body as the subject, not the object. Using the example of new Polish poetry, it analyses the changes the ﬁ gure of the human body undergoes in the era of technological syndrome, from stressing it as subjectivity, through realizing the imperfect nature of one's own - human corporeality up to the attempts at coping with these fallibilities through equipping it and enriching it with technological artiﬁ cial body parts inspired by the achievements of modern technology, or introducing the form of a closed cycle with technological achievements. The author shows how radically contemporary literature and aesthetics break the earlier obligatory taboo of the inviolability of the human body and what problems the post-human corporeality has to face. The text emphasizes the need to transform the traditional way of thinking about poetry, which does not want to be only the scream of the soul, but it undertakes the ambitious task of describing and documenting the world and the changes it undergoes. The author highlights the necessity to notice and understand one's own corporeality because it has always had a strong impact on human psyche.